Office Ergonomics Assessment dengan Menggunakan MIRTH Office - Mufti, Wahyu Fitrianda; Ramadian, Demi; Viarani M, Suci Oktri (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2020)
The computerized system is closely related to today’s office works. Computer works with high intensity of repetition and awkward posture can cause harm or risk. This can cause discomfort in several areas of the body. Therefore, an office ergonomics assessment that focuses on humans as the most important component is needed to determine the impact and causes of the discomfort problem. In this study, MIRTH Office is used as the assessment tools. The questionnaire consists of two parts, namely general information and conformity assessment. The data processing stage in this study consisted of problem identification and problem grouping. The results showed that most of the respondents experienced pain in the neck, shoulders, elbows, wrists and lower back. These results indicate the need of ergonomics intervention as early as possible to prevent the risk of musculoskeletal disorders.